Massic Activity Ratios of the NBS/NIST Tritiated-Water Standards Issued Between 1954 and 1999 - Lucas, L. L. (J Res Natl Inst Stand Technol, 2000)
As part of the preparation and calibration of three new National Institute of Standards and Technology (NIST) tritiated-water radioactivity Standard Reference Materials (SRMs), the massic-activity (activity of the sample divided by the mass of the sample) ratios of all of the available NBS/NIST tritiated-water SRMs issued between 1954 and 1999 were measured using liquid-scintillation (LS) counting. Four of the tritiated-water standards (SRMs 4361, 4926B, 4927C, and 4927D) were not available for measurement. All of the other tritiated-water standards (SRMs 4361B, 4361C, 4926, 4926C, 4926D, 4926E, 4927, 4927B, 4927E, and 4927F) were available, having been stored in flame-sealed glass ampoules. Where possible, massic-activity ratios measured by liquid-scintillation counting are compared with massic-activity ratios calculated from gravimetric dilution factors. The agreement is well within the stated uncertainties. For two of the tritiated-water standards that were not available for measurement (SRMs 4361 and 4926B), massic-activity ratios calculated from gravimetric dilution factors are available.